The uneven space distribution of first carlism: A quantitative approach - Caridad, Antonio (Huarte de San Juan. Geografía e Historia, 2018)
One of the worst explained aspects of Carlism is its uneven territorial distribution. This difference has been traditionally explained referring to the different impact of the economic crisis in each territory. In this paper I have tried to check this hypothesis and to analyse other possibilities, using quantitative criteria. In this way, I have reached the conclusion that, not only the impact of the economic crisis, but also the kind of predominant estate, the percentage of noblemen and the importance of communal land had an influence in the development of Carlism.